Using virtual simulations of future extreme weather events to communicate climate change risk - GEVELT, Terry Van (Institutional Knowledge at Singapore Management University, 2023)
Virtual simulations of future extreme weather events may prove an effective vehicle for climate change risk communication. To test this, we created a 3D virtual simulation of a future tropical cyclone amplified by climate change. Using an experimental framework, we isolated the effect of our simulation on risk perceptions and individual mitigation behaviour for a representative sample (n = 1507) of the general public in Hong Kong. We find that exposure to our simulation is systematically associated with a relatively small decrease in risk perceptions and individual mitigation behaviour. We suggest that this is likely due to climate change scepticism, motivation crowding, geographical and temporal distance, high-risk thresholds, feelings of hopelessness, and concerns surrounding the immersiveness of the virtual simulation.